Time–space intensification: Karl Polanyi, the double movement, and global informational capitalism - Ó Riain, Seán (Theory and Society, 2006)
This article advances the concept of “time–space intensification” as an alternative to existing notions of time–space distanciation, compression and embedding that attempt to capture the restructuring of time and space in contemporary advanced capitalism. This concept suggests time and space are intensified in the contemporary period – the social experience of time and space becomes more explicit and more crucial to socio-economic actors’ lives, time and space are mobilized more explicitly in individual and corporate action, and the institutionalization of time and space becomes more politicized. Drawing on Polanyi’s concepts of fictitious commodities and the double movement, and developing them through an analysis of work organization and economic development in the Irish software industry, the article argues that the concept of time–space intensification can add significantly to our understanding of key features of the restructuring of the temporal and spatial basis of economic development and work organization.
Sociology
Keywords: capitalism; double movement; fictitious commodities; social theory; time-space intensification

Globalization and contestation: A Polanyian problematic - Munck, Ronaldo (Globalizations, 2006)
The Polanyian problematic presents us with a unified, complex, and dialectical means to interpret globalization and its social contestation by diverse social and political forces. For Karl Polanyi (1886–1964), globalization as we know it would probably be conceived of as an extension of the ‘one big self-regulating market’ he discerned in his day, while his belief that ‘simultaneously a counter-movement was afoot’ provides an interpretative lens to examine the various facets of the counter-globalization movement. The Polanyian problematic of modern history as a ‘double movement’, whereby market expansion and social protection respectively lead phases, provides a useful antidote to all forms of economic reductionism when dealing with globalization on the one hand and political voluntarism with regard to contestation on the other. Basically, globalization is a human construct, and it can thus be deconstructed by society.
Sociology; Political Science
Keywords: Polanyi problem; countermovement; globalization

Economia di mercato e legame sociale: verso nuovi equilibri? - Scidà, Giuseppe (Market economy and social link: towards a new equilibrium?, 2006)
In its first part (§ 2-4), the essay presents an outline of market economy in a globalization era, highlighting its marked changes and the wide fields of its questionable nature. In the second part, some discontinuity features came out in the last decades are shown (§ 5). They are particularly referred to critical analysis and alternative experiences springing up from below, (i.e. associations, groups, movements of the civil society) and meeting in a common attempt of getting economy and people's life with all their social link close again. Afterwards (§ 6- 7), it's stressed as similar concerns can also be found in the very theories by the founder of economic discipline, Adam Smith, and somehow in the works expressing some of the most alternative positions as Karl Polanyi's. Finally (§ 8) it's presented the notion of social capital that is the subject of the present issue of Sociologia del Lavoro. Though arising a lively critical debate, potentially the notion seems to open some new scenarios in the social science in pursuit of a new equilibrium between market economy and social link.
Sociology
Keywords: POLANYI; Karl; 1886-1964; SMITH; Adam; 1723-1790; civil society; globalization; international markets; international relations; interpersonal relations; market economy; social integration; social sciences

The Role of Consensus and Social Homogeneity in the Process of Building Capitalism in Post-communist Countries - Bieliński, Jacek (KONSENS I JEDNORODNOŚĆ SPOŁECZNA W PROCESIE BUDOWANIA KAPITALIZMU W KRAJACH POSTKOMUNISTYCZNYCH., 2006)
The focus of this article is on interpretation of progress of post-communist transformations. Classical approaches, particularly those of Max Weber and Karl Polanyi, rather than modern ones are used as basis for the empirical analysis. I argue that the success of capitalist project, both now and in the past, stems from the ability to work out a general consensus about the preceding economic order. I also claim that ethnic homogeneity can be a favorable factor for the post-communist transformation, especially in its initial phase. Moreover, unlike in fully developed market systems which are more stable and socially diverse, the success of market reforms in post-communist countries negatively correlates with their diversification. One of the main goals of this analysis is to describe empirically what this consensus refers to. Survey research shows that market reforms in former socialist block run more smoothly if the level of social consensus about key values, not necessarily liberal, is high. I analyzed values and attitudes defining the consensus and also the degree of their popularity among economic elites and non-elites. Data used in the analysis comes from the first edition of European Social Survey. (English)
Sociology
Keywords: WEBER; Max; 1864-1920; capitalism; economic sociology; elite; jednorodność; konsens społeczny; markets; post-communism; post-communist transformations; postcommunism; postcommunist societies; social consensus; social homogeneity; socjologia ekonomiczna; społeczna; transformacja postkomunistyczna

The Relationship between Economics and Sociology: The Contribution of Economic Sociology, Setting out from the Problem of Embeddedness - Rizza, Roberto (International Review of Sociology, 2006)
s essay aims to analyse the most recent acquisitions in economic sociology, setting out from the problem of embeddedness. Firstly, the contribution offered by Mark Granovetter shall be illustrated, demonstrating how the interpretation proposed by this scholar is concentrated on a structural-relational perspective that tends to trace the explanation of economic phenomena to a theory of social networks. In order to enrich and integrate this approach, the contribution offered by the new-institutionalist perspective in contemporary economic sociology will be emphasised, which has focused on the social construction of economic institutions. This current has underlined, on the one hand, the cognitive dimension of embeddedness, related to the way in which the uniformities structured by mental processes limit economic reasoning, and, on the other, the cultural dimension of embeddedness, concerning the role of collectively shared representations in the formation of economic goals. It will be concluded by illustrating the acquisitions of some theoretical perspectives linked to the polanyian tradition that have developed a 'plural' conception of economy, founded on the emphasis of socio-regulative principles, such as those of exchange, redistribution and reciprocity, which, in becoming hybrid, give shape to variable and historically anchored economic worlds. The concept of embeddedness roots historically and transmits a vision of economic processes as inseparable from noneconomic institutions
Sociology
Keywords: GRANOVETTER; Mark; economic research; economic sociology; embeddedness; industrial management; social sciences; socioeconomic factors; socioeconomics

Karl Polanyi et les monnaies modernes : un réexamen - Blanc, Jérôme (Contributions à une sociologie des conduites économiques, 2006)
Karl Polanyi a établi une célèbre distinction entre "all purpose money", caractéristiques des sociétés modernes, et "special purpose money", caractéristiques des sociétés anciennes. C'est la conception polanyienne des monnaies modernes qui est critiquée dans ce texte : non seulement elle conduit à considérer que les sociétés modernes ne connaissent pas de "special purpose money", mais en plus elle ne permet pas de renouveler la conception courante de la monnaie (sous-entendu moderne) qui en fait un moyen de paiement universel. ENG translation: Karl Polanyi has established a famous distinction between "all purpose money" characteristic of modern societies, and "special purpose money", characteristic of ancient societies. It is the Polish conception of modern currencies that is criticized in this text: not only does it lead to the view that modern societies do not know a "special purpose money", but also does not allow to renew the current conception of Currency (modern underlining) which makes it a universal means of payment.
Sociology
Keywords: Monnaie moderne. Pratiques monétaires. Polanyi. Monnaies parallèles. Fongibilité. Cloisonnements.; boundaries; fungibility; modern money; monetary uses; parallel currencies

Governing the Market: The "Political" and the "Economic" in the Restructuring of the "Third World" - Makki, Fouad (Conference Papers – International Studies Association, 2006)
My intention in this paper is to rethink the central contentions of "Globalization Theory" with respect to the relationship of the "state" to the "economy." I will do so via a consideration of recent discussions of the formation of the modern states system within the discipline of International Relations, and Karl Polanyi?s suggestive notion of the "double movement" presently enjoying a revival in sociological studies of the conjuncture of the 1990s. The paper concludes with reflections on how these critical reflections might make it possible to gain a betterappreciation of the current neoliberal restructuring of the erstwhile "Third World." PAT.-Conference Proceeding
Political Science; Sociology
Keywords: economic structure; economics; globalization; international markets; international trade

The Dark Side of Embeddeness: The Construction of Economic space and Prestige in Italy 1896-1907 - Polillo, Simone (2006)
The creation of a national economic space is the necessary structural condition for the unfolding of the "self-protective" measures of society that Polanyi analyzed for the post-WWI period, and that he saw as more generally arising in response to free market policies. A national economic space is itself the product of specific institutional arrangements, in particular the state agencies that allow the state to centralize the monetary system in its own hands: in the modern period, these have been central banks. By analyzing a longitudinal sample of the minutes of the meetings of the governing body of the Bank of Italy in its crucial transitional period at the turn of the century (1896-1907), this paper attempts to trace the historical process by which the Italian economy came to be understood as a national space. It shows that the creation of an area of economic prestige measured by the technical success of the central bank and the strength of its relationship with the Treasury was a crucial achievement of the liberal state. ..PAT.-Unpublished Manuscript
Sociology
Keywords: Italy; World War I; banking industry; central bank; embeddedness; manuscripts; monetary policy; money; saving and investment; self-protective measures; state

Lavoro e società industriale. Da Adam Smith a Karl Polanyi - Rosa, Michele La; Rizza, Roberto; Zurla, Paolo (FrancoAngeli, 2006)
KM translate: The volume aims to provide a contribution to the knowledge of the ways of birth and consolidation of the sociological discourse on the economy, at work and their transformations connected to the process of industrialization. The goal, mainly educational, is pursued through the analysis of the contributions that Karl Marx, Emile Durkheim, Max Weber, Joseph Schumpeter, Karl Polanyi, Frederick Taylor and Elton Mayo have offered in this regard. The treatment of these authors, whose total or partial belonging to the sociological context is out of the question, was preceded by a brief analysis of others such as Adam Smith, Charles Babbage and Andrew Ure who, although not strictly belonging to this disciplinary area,
Economics; Sociology
Keywords: DURKHEIM; Emile; MARX; Karl; 1818-1883; SMITH; Adam; 1723-1790; business & economics - labor; economic sociology; industrial revolution; industrialization; sociology of work

Retelling the Great Transformation - Steinberg, Marc (2006)
In this paper I partly retell Polanyi's narrative of the industrial revolution found in his Great Transformation. I discuss how new labor laws consolidated in the 19th century created a legal structure of coerced contractual labor, that did not fit the ideals of free market economics. My retelling focuses on how capitalists in some industries relied on legal coercion of their workers as a means of discipline and labor process control. Through this retelling I demonstrate that Polanyi was still beholden to neo-classical economics in his historical account, errantly seeing the rise of a free market in labor with the Poor Law reforms of 1834 when in fact no such freedom existed. Therefore, he could not provide a fully-fledged institutional analysis of economic embeddedness that lies at the core of his theory. To realize a fully-developed institutional analysis I argue that we need to bring class conflict back into the narrative of institutional change through an analysis of legality and its transformation. I partly map out the outlines of a revised institutional analysis that places emphasis on the spatial organization of power, with 'stateness' conceptualized as a variable in which political power (and more especially authority) is scrutinized as historically accreted institutional structures. I also emphasize the historically specific role of the 'local state' in this narrative. ..PAT.-Unpublished Manuscript
Sociology
Keywords: capitalists & financiers; criminal procedure; industrial laws & legislation; industrial relations; institutional embeddedness; labor laws & legislation; labour laws & legislation; law; quality control